Effects of age composition on academic achievement in college classrooms - Richard J. Novak (Adult Education Research Conference, 1993)
The research explores the effects of age composition on academic achievement in college classrooms. The presence of adults influences expectations for normative behaviors with respect to the role of student and thus affects the classroom social climate and academic performance.